Application of the institute of confiscation of property by the Russian empire in right-bank Ukraine at the end of XVIII - early XIX century - Broslavsky, Volodymyr (Actual problems of law (Aktual’ni problemi pravoznavstva), 2021)
Russian and Soviet historiography propagated the myth of the painless accession of Right-Bank Ukraine to the Russian Empire. The main reason was the decline of the Polish-Lithuanian Commonwealth and its divisions, provoked by Prussia and Austria. However, a deeper analysis of regulations and the source base reveals the fact of occupation of the region by the Russian Empire and the peculiarities of its occupation policy. One of the levers of which was the institution of confiscation of property. The study examines the features of the application of the institution of confiscation of property by the Russian Empire in the Right-Bank Ukraine in the late XVIII - early XIX centuries. The normative legal acts of the Russian Empire were analyzed, which provided in which cases confiscation of property could be applied and regulated its procedure. Traditionally, confiscation of property was used as a punishment for mercenary crimes or crimes against state security. However, the Russian Empire used the institution of confiscation of property as an element of the empire’s occupation policy. It is established that using the institution of confiscation of property on the Right Bank of Ukraine in the period under study, the Russian Empire primarily tried to achieve political goals. By blackmailing the property of the nobility and the Catholic and Uniate clergy, Russian officials managed to keep the occupied region under the rule of the Russian Empire. Thus, for participating in the uprising against the Russian Empire, illegal departure from its borders or participation in Napoleon’s war against the Russian Empire provided for the confiscation of not only existing property but also future heritage. Economic terror was also used to legitimize the occupation of the region. The main lever of influence on the nobility and clergy of the region was also the threat of confiscation of property. The local population was forced to make a choice: either to take an oath of allegiance to the Russian Empire and preserve the property, or to refuse and urgently sell it and leave the empire. To weaken the economic position of the Catholic and Uniate churches, the Russian government also used the institution of confiscation: alienating real estate to state ownership and assigning money to the clergy loyal to the empire.